Efeitos da vinhaça sore a dispersão de argila de amostras de latossolos - Ribeiro, Antônio Carlos; Ferreira de Novais, Roberto; Fernandino de Castro Bahia Filho, Antônio (Revista Ceres, 2025)
The effect of vinasses from two different sources on clay dispersion in samples of six Latosols was studied under laboratory conditions. The clay determination was done by the pipete method, using 0.5 N NaOH as the dispersing solution in one treatment and compared with treatments in which this solution was water or the vinasses. In relation to water, the vinasses caused higher dispersion in the medium-textured soils an floculation in the clayey-textured soils. The vinasse with higher cation concentration had a lesser effect on clay dispersion in all soils studied. The effect of the vinasses on dispersion of the soil clay fraction depends on the concentration and ratio of cations ins the vinasse as well as on the nature of the clay.